COMT genotype, gambling activity, and cognition. (September 2015) - Grant, Jon E.; Leppink, Eric W.; Redden, Sarah A.; Odlaug, Brian L.; Chamberlain, Samuel R.
Abstract: Neuropsychological studies of adults with problem gambling indicate impairments across multiple cognitive domains. Catechol-O-methyltransferase (COMT) plays a unique role in the regulation of dopamine in the prefrontal cortex, and has been implicated in the cognitive dysfunction evident in problem gambling. This study examined adults with varying levels of gambling behavior to determine whether COMT genotype was associated with differences in gambling symptoms and cognitive functioning. 260 non-treatment-seeking adults aged 18–29 years with varying degrees of gambling behavior provided saliva samples for genotyping COMT val158met (rs4680). All subjects underwent clinical evaluations and neurocognitive assessment of decision-making, working memory, and impulsivity. The Val/Val COMT genotype was associated with the largest percentage of subjects with gambling disorder (31.8%), a rate significantly different from the Val/Met (13.2%) group (p = 0.001). The Val/Val COMT group was also associated with significantly more gambling disorder diagnostic criteria being met, greater frequency of gambling behavior, and significantly worse cognitive performance on the Cambridge Gamble Task (risk adjustment and delay aversion) and the Spatial Working Memory task (total errors). This study adds to the growing literature on the role of COMT in impulsive behaviors by showing that the Val/Val genotype was associated with specific clinical and cognitive elements among young adults who gamble, in the absence of differences on demographic measures and other cognitive domains. Future work should consider using genotyping to explore whether certain polymorphisms predict subsequent development of impulsive behaviors including gambling disorder, and treatment outcomes. Highlights: This study is the first to examine COMT genotypes in a large sample of individuals with varying levels of gambling behavior. Subjects with the Val/Val genotype exhibited worse gambling symptoms. Val/Val genotype was associated with impaired risk adjustment, delay aversion, and spatial working memory problems.